1 / 25

250 likes | 352 Vues

Algebra. Chapter 1 LCH GH. p.3. Simplify ( i ). multiply each part by x. =. factorise the top. =. Divide top & bottom by (x-3). =. p.3. Simplify (ii). +. Multiply second part above and below by -1 So that both denominators are the same. +. Factorise the top. p.3. Simplify

Télécharger la présentation
## Algebra

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**Algebra**Chapter 1 LCH GH A Roche**p.3**Simplify (i) multiply each part by x = factorise the top = Divide top & bottom by (x-3) =**p.3**Simplify (ii) + Multiply second part above and below by -1 So that both denominators are the same + Factorise the top**p.3**Simplify 1. 4x(3x2 + 5x + 6) – 2(10x2 + 12x) 4x(3x2 + 5x + 6) – 2(10x2 + 12x) = 12x3 + 20x2 + 24x – 20x2 - 24x = 12x3**p.3**Simplify 2. (x + 2)2 + (x - 2)2 - 8 Expand the squares (x + 2)2 + (x - 2)2 - 8 = (x2 + 4x + 4) + (x2 - 4x + 4) - 8 = 2x2**p.3**Simplify 3. (a + b)2 - (a - b)2 – 4ab Expand the squares (a + b)2 - (a - b)2 – 4ab = (a2 + 2ab + b2) - (a2 – 2ab + b2) – 4ab = a2 + 2ab + b2 - a2 + 2ab - b2 – 4ab = 0**p.3**Simplify 4. (2a + b)2 – 4a(a + b) Expand (2a + b)2 – 4a(a + b) = (4a2 + 4ab + b2) - 4a2 – 4ab = 4a2 + 4ab + b2 - 4a2 – 4ab = b2**p.3**Factorise 5. x2 + 3x x2 + 3x = x(x + 3) HCF Factorise 6. 3xy – 6y2 HCF 3xy – 6y2 = 3y(x - 2y)**p.3**Factorise 7. a2b + ab2 a2b + ab2 = ab(a + b) HCF Factorise 8. 9x2 – 16y2 Difference of 2 squares 9x2 – 16y2 = (3x – 4y)(3x + 4y)**p.3**Factorise 9. 121p2 – q2 Difference of 2 squares 121p2 – q2 = (11p – q)(11p + q) Factorise 10. 1 – 25a2 Difference of 2 squares 1 – 25a2 = (1 – 5a)(1 + 5a)**p.3**Factorise 11. x2 – 2x - 8 -8 (1)(-8) (2)(-4) (4)(-2) (8)(-1) Quadratic factors Which factors add to -2? x2 – 2x - 8 = (x +2 )(x - 4 ) = (x )(x ) Factorise 12. 3x2 + 13x - 10 -10 (1)(-10) (2)(-5) (5)(-2) (10)(-1) 3x2 + 13x - 10 Quadratic Factors Check! +15x = (3x )(x ) = (3x – 2)(x + 5) -2x**p.3**Factorise 13. 6x2 - 11x + 3 6x2 (6x)(x) (3x)(2x) 6x2 - 11x + 3 Quadratic Factors Check! -9x = ( )( ) = (3x )(2x ) = (3x – 1)(2x - 3) +3 (1)(3) (-1)(-3) -2x **p.7 Example**If a(x + b)2 + c = 2x2 + 12x + 23, for all x, find the value of a, of b and of c. a(x + b)2 + c = 2x2 + 12x + 23 Expand the LHS • a(x2 + 2xb + b2) + c = RHS Observe that the LHS is a Quadratic Expression in x • ax2 + 2axb + ab2 + c = RHS • Equate coefficients of like terms • (a)x2 + (2ab)x + (ab2 + c) = 2x2 + 12x + 23 • 2ab = 12 • a = 2 • ab2 +c = 23 • 2(2)b = 12 • (2)(3)2 +c = 23 • 4b = 12 • 18 +c = 23 • b = 3 • c = 5**p.7 Example**(ii) If (ax + k)(x2 – px +1) = ax3 + bx + c, for all x, show that c2 = a(a – b). (ax + k)(x2 – px + 1) = ax3 + bx + c Expand the LHS • ax(x2 –px + 1) +k(x2 –px + 1) = RHS • ax3 - apx2 + ax + kx2 –kpx + k = RHS • (a)x3 + (-ap + k)x2 + (a - kp)x + k = ax3 + 0x2 + bx + c • Equate coefficients of like terms • k = c • a = a • k - ap = 0 • a – kp = b • c - ap = 0 • a – c(c/a) = b • a – c2 /a = b • c = ap • a – b = c2 /a • p = c/a • a(a – b) = c2**p.9 Example**Write out each of the following in the form ab, where b is prime: (i) 32 (ii) 45 (iii) 75 Divide by the largest square number: 1 4 9 16 25 36 49 64 81 100 121 144 169 (i) 32 = (16 x 2) • = 162 • = 42 (ii) 45 = (9 x 5) • = 35 • (iii) 75 =(25 x 3) • = 53**p.9 Example**Express in the form , a, b N : (iv) (v) Divide by the largest square number: 1 4 9 16 25 36 49 64 81 100 121 144 169 (iv) (v)**p.9 Example**(vi) Express in the form k2. (vi)**p.9 Example**(i) Express 18 + 50 - 8 in the form ab, where b is prime. (ii) 20 - 5 + 45 = k5; find the value of k. Divide by the largest square number: 1 4 9 16 25 36 49 64 81 100 121 144 169 (i) 18 + 50 - 8 = (9 x 2) + (25 x 2) - (4 x 2) • = 32 + 52 – 22 • = 62 (ii) 20 - 5 + 45 • = (4 x 5) - 5 + (9 x 5) = 25 - 5 + 35 • = 45**Examples of Compound Surds**P.10 • 1 + 5 a + b • a- b • 3- 24 • a- b • 13- 7**Conjugate Surds**P.10 When a compound surd is multiplied by its conjugate the result is a rational number. • Conjugate 2 Compound Surd • Conjugate 1 • a - b • - a + b a + b • a - b • a + b • -a - b We use this ‘trick’ to solve fractions with compound denominators • a + b • a - b • - a + b**p.10 Example**Show that Multiply top and bottom by conjugate of denominator Note that the bottom is difference of 2 squares 1 – 3 Q.E.D.**p.11**Solving Simultaneous Equations For complicated simultaneous equations we use the substitution-elimination method**p.12 Example**Solve for x and y the simultaneous equations: x + 1 – y + 3 = 4, x + y – 3 = 1 2 3 2 2 Get rid of fractions by Multiplying x + 1 – y + 3 = 4 2 3 x + y – 3 = 1 • 2 2 • (6)(x + 1)– (6)(y + 3) = (6)4 • 2 3 2x + 2(y – 3) = 2(1) • (3)(x + 1)– (2)(y + 3) = 24 • 2 2 3x + 3 – 2y - 6 = 24 2x + y – 3 = 1 • 3x– 2y = 27 • 2x + y = 4 • Now solve these simultaneous equations in the normal way • x = 5 and y = -6**p.12-13 Example**Solve for x, y and z: x + 2y + z = 3 5x – 3y +2z = 19 3x + 2y – 3z = -5 1 2 Label the equations 1, 2 & 3 • Eliminate z from 2 equations 3 5x – 3y +2z = 19 3x + 2y – 3z = -5 2 3 -2x - 4y -2z = -6 x -2 3x + 6y + 3z = 9 x 3 1 1 5 • 3x - 7y = 13 • 6x + 8y = 4 4 • Now solve simultaneous equations 4 & 5 in the usual way We find that: x = 2 y = -1 x + 2y + z = 3 • Sub these values into equation 1 • (2) + 2(-1) + z = 3 • z = 3**p.13**Note: If one equation contains only 2 variables then the other 2 equations are used to obtain a second equation with the same two variables • 3x + 2y - z = -3 • 5x – 3y +2z = 3 • 5x + 3z = 14 1 • e.g. Solve 2 3 • Here, from equation 1 and 2, y should be eliminated to obtain an equation in x and z, which should then be used with equation 3

More Related